Influence of Different Organic Acids on Characteristics of Lignin-Based Adhesives from Breadfruit Skin Biorefinery - Jacindana Aurel Hadiyanto; Muhammad Adly Rahandi Lubis; Efri Mardawati (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study aims to analyze and synthesize research findings related to the effect of various types of organic acids on the characteristics of breadfruit (Artocarpus altilis) peel lignin as a raw material for bio-based adhesives and to identify its potential use as an alternative environmentally friendly adhesive. The study uses a literature study method sourced from national and international scientific articles obtained through the Scopus, ScienceDirect, Google Scholar, and SpringerLink databases with a publication range of 2014–2024. The analysis was conducted on studies discussing lignin extraction, precipitation processes using organic acids, lignin characterization, and its application in lignin-based adhesive formulations. In addition, a bibliometric analysis using VOSviewer on 114 publications was conducted to map research developments, keyword trends, and the relationship between dominant research themes. The results of the bibliometric analysis indicate that the topics of lignin, bio-based adhesives, biomass valorization, and organic acid treatment have become the main focus of research in the last decade. The results of literature synthesis indicate that the use of organic acids, such as acetic acid, maleic acid, and citric acid, produces different lignin characteristics, especially in chemical structure, phenolic group content, thermal stability, and adhesive reactivity. Characterization using FTIR, TGA, NMR, and SEM indicates that breadfruit peel lignin has high potential as a raw material for bio-based adhesives for more sustainable wood and plywood applications